MUHAMMADIYAH PROCESSING STRATEGY IN FILM WORKS IN THE MILLENIAL ERA - Silvira, Yuike; Lailan Arqam, Mhd (Al-Mubin, 2024)
Technological developments and globalization have a very broad impact on today's society and drive a change in the way people view and culture life in various aspects. Today's people can easily access and obtain the information they need through a variety of media, including religious information. People can easily learn religion through various platforms. This is what encourages religious practitioners to change the way of worship, and it is a challenge for the Muslims themselves to use this technology in effective and efficient worshipping activities, especially for major Islamic organizations in Indonesia such as the Muhammadiyah because Da'wah in the digital age has an impact on the da'wah world today in that it offers convenience, which will almost eliminate the boundaries of time and location between people. In order to accomplish this, how can we as millennials prepare for and adapt to the problems of da'wah in the millennial era by mastering technology, social media, and the internet to the greatest extent possible? The purpose of this study is to be aware of how was da’wah stategy was conducted by Muhammadiyah's efforts as a millennial-era Islamic da'wah movement. The research technique utilized in this article is called the library research method, and it entails the researcher analysing or reviewing journals, books, notes, etc., as well as looking at the findings of previous studies and other data gathered. relevant. Results indicate that Muhammadiyah created 8 films dealt with Muhammadiyah figures, whereas 5 were produced directly by LSBO PP Muhammadiyah